Kinerja Dinas Tenaga Kerja Di Kota Pekanbaru - Kristina Purba; Khairul Amri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The Pekanbaru City Manpower Service has the main task of carrying out some of the city's regional government affairs in the field of labor. Providing guidance, controlling, supervising and providing training to workers is a function of the employment service which has an influence on the level of unemployment. This research aims to analyze and determine the performance of the Manpower Service in Pekanbaru city as well as to analyze and find out the factors inhibiting the performance of the Manpower Service in Pekanbaru city. This research uses performance theory from Agus Dwiyanto (2018) which provides 5 assessment indicators, namely: Productivity, Service Quality, Responsiveness, Accountability and Accountability. The method used in this research is a qualitative approach with data collection techniques in the form of observation and interviews. The results of this research are that the performance of the Manpower Department in Pekanbaru city has not yet been achieved optimally. This can be seen from the productivity indicators which can be seen from the absence of training for job seekers so that there is no supervision of trained job seekers and there are still several inhibiting factors. others such as limited APBD, there are still companies that do not know their obligations and limited work delivery personnel.